2013
DOI: 10.1111/gcb.12125
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic matter quality influences mineralization and GHG emissions in cryosols: a field‐based study of sub‐ to high Arctic

Abstract: Arctic soils store large amounts of labile soil organic matter (SOM) and several studies have suggested that SOM characteristics may explain variations in SOM cycling rates across Arctic landscapes and Arctic ecosystems. The objective of this study was to investigate the influence of routinely measured soil properties and SOM characteristics on soil gross N mineralization and soil GHG emissions at the landscape scale. This study was carried out in three Canadian Arctic ecosystems: Sub-Arctic (Churchill, MB), L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 85 publications
3
22
0
Order By: Relevance
“…Soil WC, C total , and clay content explained another 7% of the variation in N 2 O -flux , which agrees with Clemens et al (1999). Clay content influenced N 2 O formation by affecting the soil moisture regime, whereas soil carbon (C total ) may interfere with N 2 O formation (Paré and Bedard-Haughn 2013). All of these parameters, except for clay content, were significantly influenced by the presence of trees.…”
Section: Nitrogen Dynamicssupporting
confidence: 79%
“…Soil WC, C total , and clay content explained another 7% of the variation in N 2 O -flux , which agrees with Clemens et al (1999). Clay content influenced N 2 O formation by affecting the soil moisture regime, whereas soil carbon (C total ) may interfere with N 2 O formation (Paré and Bedard-Haughn 2013). All of these parameters, except for clay content, were significantly influenced by the presence of trees.…”
Section: Nitrogen Dynamicssupporting
confidence: 79%
“…To date, most incubation studies have been relatively short term (weeks to a few months) and thus are assessments of the most bioavailable components of SOM. Some studies have combined chemical or physical characterizations with incubations in an effort to relate SOM composition to decomposition rates or to identify indices of decomposability (e.g., White et al, 2002White et al, , 2004Weintraub and Schimel, 2003;Waldrop et al, 2010;Diochon et al, 2013;Paré and Bedard-Haughn, 2013;Pengerud et al, 2013;Treat et al, 2014). In general, SOM of higher quality (less decomposed and rich in polysaccharides and proteins) is positively related to mineralization rates.…”
Section: Characterization Of the Quality And Decomposability Of Organmentioning
confidence: 99%
“…In another case, Wild et al (2014) showed that the mineralization rates of surface organic soil, mineral subsoil, and cyroturbated organic material in the subsoil (all from the active layer) were each differentially limited by the availability of labile organic carbon substrates or nitrogen. Importantly, however, many of the conditions impacting mineralization rates in incubation studies are indicative of factors responsible for variations in overall SOC storage, turnover times, and the intrinsic relative degradation state of SOM on subregion, landscape, and local scales (e.g., Kaiser et al, 2007;Hugelius et al, 2012;Paré and Bedard-Haughn, 2013;Pengerud et al, 2013).…”
Section: Characterization Of the Quality And Decomposability Of Organmentioning
confidence: 99%
“…After the temperatures peak in summer, C release would decrease, owing to labile C components lost and decreasing temperature in the "later stage of the growing season" (LG). Nevertheless, litter or organic matter of different quality may exhibit various responses to freezing and thawing dynamics under a scenario of climate change (Pare and Bedard-Haughn, 2013). Many more works must, however, be carried out to more clearly understand litter C release processes in cold biomes.…”
Section: Introductionmentioning
confidence: 99%